Significant effect of NSP‐ase enzyme supplementation in sunflower meal‐based diet on the growth and nutrient digestibility in broilers. Issue 2 (23rd July 2016) - Bilal, M.; Mirza, M. A.; Kaleem, M.; Saeed, M.; Reyad‐ ul‐ferdous, Md.; Abd El‐Hack, M. E.
Summary: The response of broiler chickens to 3 levels of sunflower meal and 2 levels of NSP‐ase enzyme combination (with and without) was investigated in 3 × 2 factorial arrangement under complete randomized design (CRD). A total of 240 Hubbard broiler chicks were fed on practical mash diets having 2950 kcal of ME and 21% CP from 1 to 42 days of age. The BW gain was not significantly reduced when 25% SFM was added in the diets during 1 to 42 days of age. Supplementation of NSP‐ase in broiler diets (day 1–42 overall) demonstrated non‐significant differences (p < 0.05) across the treatments in terms of FI and BWG. The difference in feed:gain at 15% or 20% SFM was observed to be non‐significant. Replacement of SBM with SFM or inclusion of SFM at higher level (25%) increased/deteriorated FCR. The addition of exogenous NSP‐ase showed a significant improvement (p < 0.01) in feed:gain. The improvement was clearly demonstrated when SFM was added to the experimental diet at 15% or even 20%. Supplementation of NSP‐ase at the 25% inclusion level could not, however, sustain the beneficial effect, which was possibly due to excessively high dietary CF. No difference was noted across the treatments regarding carcass response. Relative gizzard weight and intestinal weight were observed to be improved in birds consuming higher levels of SFM (p = 0.00). The digestibility of CF was observed to improve when SFM was used at 20% and 25% in the diets. No improvement in the digestibility of CF was observed with NSP‐ase supplementation, which meant other factors were clearly involved. Supplementation of NSP‐ase improved FCR up to 20% SFM. At 25% SFM, no improvement in the digestibility of CF was observed with NSP‐ase supplementation.